Flexural Behaviour of Lightweight Reinforced Concrete Beams Internally Reinforced with Welded Wire Mesh - Pavithra Chandramouli; Dinesh Muthukrishnan; Venkatesh Sridhar; Veerappan Sathish Kumar; Gunasekaran Murali; Nikolai Ivanovich Vatin (Buildings, 2022)
Lightweight clay aggregate (LECA) is manufactured by heating clay with no lime content in the kiln; as a result, the water evaporates and angular clay balls with pore structures are obtained. LECA possess internal curing properties as any other lightweight aggregate due to their pore structure and higher water absorption capacity. In this work, experimental and analytical behaviour using LECA as a 100% replacement for coarse aggregate to make lightweight concrete (LWC) beams was studied. The LWC beams were compared to the conventional concrete beams in load-deflection, energy absorption capacity, and ductility index. Internal mesh reinforcement using welded wire mesh (WWM) of (4 layers of 15 mm square spacing, 4 layers of 10 mm square spacing, and 4 layers of 15 mm and 10 mm mesh placed alternatively) was provided to enhance the load-carrying capacity of the LWC beam without increasing the dimensions and self-weight of the beams. The beam internally reinforced with WWM exhibited higher load carrying capacity and withstood more significant deflection without sudden failure. The internal reinforcement of WWM is provided to make steel rebars, and WWM works monolithically while loading; this will reduce the stress on tension bars and increase load-carrying capacity. Finally, the generated analytical findings agreed well with the experimental data, demonstrating that the analytical model could mimic the behaviour of LWC beams with WWM.